PESQUISA E ANÁLISE DE DADOS ONCOLÓGICOS DA ÁREA DE ABRANGÊNCIA DA 17ªCRS - CEMBRANEL, ANGÉLICA; NONNENMACHER, CARINE L.; SILVA, LUIZ A. A. D.; SONTAG, ROSILEI; ARAÚJO, MÁRCIO U. D. (Salão do Conhecimento, 2013)
Resumo